Pengaruh Brand Awareness dan Celebrity Endorsement Terhadap Blackpink sebagai Brand Ambassador Tokopedia Guna Meningkatkan Brand Image - Oktaviyani, Dina; Arqy Ahmadi, Mirzam (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The partnership between Tokopedia and Blackpink as brand ambassadors has become a highlight in the marketing world. The development of communication technology and globalization has had a major influence on culture, including in Indonesia, with the emergence of the Korean Wave or Hallyu phenomenon, especially K-Pop. The popularity of K-Pop influences consumer behavior in making purchasing decisions. This study discusses the influence of Brand Awareness and Celebrity Endorsement on Blackpink as Tokopedia's brand ambassador in improving brand image. Through a qualitative approach that is a literature review, this study examines whether these factors influence Blackpink's role and its impact on Tokopedia's brand image. The results show that Brand Awareness and strong celebrity support can increase positive perceptions, visibility, and credibility of Tokopedia among consumers. This study concludes that celebrity endorsement is effective in improving Tokopedia's brand image in the Indonesian e-commerce market.